A Content Analysis of Posts to an Online Support Forum for "Girl Lovers". Issue 5 (4th July 2022) - Cantor, Nicole; Yucel, Ebru; Mitchell, Damon; Angelone, DJ
ABSTRACT: The internet is an effective tool for studying the cognitive distortions among those with a sexual attraction to children. Identified through previous works, users of an online "boy love" forum were found to present a variety of justifications for adult-child sexual relations. The current study extends this line of inquiry, analyzing posts from an online "girl love" forum. We found that the most common justification to appear reflected a belief that societal attitudes and authority figures were to blame for the harms caused by adult-child sex. We also found that the forum provided users with support and reinforcement for such distorted beliefs. Overall, online forums provide a window into the cognitive life of individuals with a sexual attraction to children, and one that reflects beliefs that may be largely unexpressed in the confines of forensic treatment settings.